Potret Pendidikan Islam dalam Perspektif Teori Sosial Interaksionisme Simbolik - Indarsih, Fajar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) STIB Banyuwangi, 2022)
The challenges and obstacles of Islamic education are increasingly complex with the times. Islamic education can no longer maintain the old ways and methods in socialization, promotion, and teaching and learning systems. One of the efforts to transform Islamic education is the openness of receiving research results through social approaches, such as targeting Islamic educational institutions through social theories. The research method uses qualitative with the type of literature research. Analysis uses descriptive methods, while the data collection process focuses on literature review. The result of the study of this article is the urgency of transforming Islamic education formally and in substance, dlohir and mental. In symbolic interactionism theory, it is important to beautify the inside and out. The external appearance of Islamic education is in the form of various facilities, facilities and infrastructure. The beautiful appearance of buildings and skyscrapers has implications for people's views to give a positive assessment. If the formal display has been able to hypnotize the Muslim community, then their response in the form of trust in Islamic educational institutions is stronger. In addition to the formal look or outer appearance, strengthening the inner look is no less important. Islamic educational institutions are obliged to improve achievements in all fields, especially achievements in the fields of religion, science and other general sciences. With these various achievements, the community must have seen that Islamic educational institutions have been able to respond to the times with a distinctive characteristic is the integration of student science including cognitive, affective, and psychomotor